The role and place of the pharmacist-cosmetologist in the choosing and implementation of a cosmetology procedure for hair removal - N. O. Tkachenko; T. V. Mahanova; H. I. Makurina; N. V. Hrinivetska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2023)
In modern cosmetology, the issue of the availability of highly qualified specialists in accordance with the needs of the industry and the implementation of effective cosmetology procedures is acute, which actualizes research on the formation of a patient-centered model of providing medical and pharmaceutical assistance of aesthetic cosmetology.